PUDING 4 BINTANG SEBAGAI ASUPAN GIZI UNTUK CEGAH STUNTING DI DESA SEMBALUN LAWANG - Dzulqaidah, Intan; Sari, Khopipah Wandan; Wardini, Tira Ruhiana; Andrianu, Ferdi; Alimajaya, Ahda; Andriansyah, Andriansyah; Multazam, M. Jauhari; Aqila, Qorina; Amalia, Winda Rizki; Parwati , Popy Yuli (Universitas Mataram, 2023)
Stunting is a chronic nutritional disorder that affects the growth and development of children. Stunting is still a problem that needs to be addressed in Sembalun Lawang Village. Prevention of stunting needs to be implemented to reduce the incidence of stunting in Sembalun Lawang Village. Stunting can be prevented through good nutrition for pregnant women and children in their toddler years. Pudding 4 stars is a form of processed healthy food that can meet nutritional intake for pregnant women and toddlers. The purpose of this activity is to increase the knowledge of mothers and expectant mothers regarding stunting, balanced nutrition, and healthy food processing. The method of implementing the activity is by conducting counseling related to stunting and balanced nutrition as well as demonstrations of making healthy food. The results of this activity increase the knowledge of mothers and prospective mothers regarding the dangers of stunting and how to prevent it, namely through the provision of good nutrition. Through this activity it is expected to be able to reduce the incidence of stunting in Sembalun Lawang Village.